2013
DOI: 10.1136/bmjopen-2013-003423
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, treatment and control in national surveys from England, the USA and Canada, and correlation with stroke and ischaemic heart disease mortality: a cross-sectional study

Abstract: ObjectiveComparison of recent national survey data on prevalence, awareness, treatment and control of hypertension in England, the USA and Canada, and correlation of these parameters with each country stroke and ischaemic heart disease (IHD) mortality.DesignNon-institutionalised population surveys.Setting and participantsEngland (2006 n=6873), the USA (2007–2010 n=10 003) and Canada (2007–2009 n=3485) aged 20–79 years.OutcomesStroke and IHD mortality rates were plotted against countries’ specific prevalence da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
282
8
32

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(370 citation statements)
references
References 24 publications
34
282
8
32
Order By: Relevance
“…Of note, 45.9% of the patients from the Ivanovo region achieved the recommended blood pressure targets of less than 140/90 mmHg. These findings were consistent with those from a recent observational study, which collected data from the general practice in Italy in 2012-2013, which reported that about 60% of patients achieved the recommended blood pressure target [9], as well as in other recent report from European countries [10][11][12]. It should be also noted that among various factors potentially involved for the achievement of BP control in this population, medical education (mostly including advices on alcohol consumption, smoking cessation and weight reduction) represents the most relevant one, whereas presence of antihypertensive drug therapies seems to have relatively limited impact on the achievement of blood pressure goals.…”
supporting
confidence: 92%
“…Of note, 45.9% of the patients from the Ivanovo region achieved the recommended blood pressure targets of less than 140/90 mmHg. These findings were consistent with those from a recent observational study, which collected data from the general practice in Italy in 2012-2013, which reported that about 60% of patients achieved the recommended blood pressure target [9], as well as in other recent report from European countries [10][11][12]. It should be also noted that among various factors potentially involved for the achievement of BP control in this population, medical education (mostly including advices on alcohol consumption, smoking cessation and weight reduction) represents the most relevant one, whereas presence of antihypertensive drug therapies seems to have relatively limited impact on the achievement of blood pressure goals.…”
supporting
confidence: 92%
“…A correct anti-hypertensive drug therapy combined with dietary and lifestyle modifications 30 attenuate the adverse effects of BP on cardiovascular health; however adequate and sustained 31 control of BP using these combined approaches is only achieved in ~60-70% of hypertensive 32 patients [3]. Therefore, the primary prevention of hypertension becomes a priority to 33 minimise the population burden of hypertension and nutritional and lifestyle approaches are 34 unanimously recognised as fundamental components of primary prevention programmes [4].…”
mentioning
confidence: 99%
“…However, it was lower than that found in a study conducted in Florianopolis with adults aged 20 to 50, in which the prevalence reached 40.1% (20) . Internationally, it appears that the prevalence of hypertension in Canada was 19.5%, lower than in the US (29%) and England (30%) (21) . It should be noted that in 2000, the prevalence of hypertension in the world population was 25% and the estimate for 2025 is 29% (22) .…”
Section: Discussionmentioning
confidence: 99%